Core Tenets of Central Venous Access in Children - Leo, Madeline E.; Gill, Anne E. (Seminars in Interventional Radiology, 2025)
Central venous access device (CVAD) placement is a common procedure for outpatient and inpatient pediatric interventional radiology practices. The principles of CVAD placement in pediatrics are similar to those in adults; however, certain clinical parameters must be considered when choosing the optimal type of line, size of catheter, and location for pediatric patients. The vessel lumen to catheter ratio is of utmost importance, and unique techniques may be necessary to facilitate bedside procedures. As in adults, all CVAD placements confer some level of risk. This review article discusses vascular anatomy, CVAD procedural techniques, and complications specifically concerning venous access in children.
Keywords: pediatric; interventional radiology; venous access; PICC; central catheter